Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932 - Irigoitia, Manuel M.; Cantatore, Delfina M.p.; Incorvaia, Inés S.; Timi, Juan T. (Zootaxa, 2016)
The olfactory sacs of 488 specimens belonging to 18 species of rajid and arhynchobatid skates from the Argentine Sea were sampled for parasites. No parasitic copepods were found in 11 host species, but siphonostomatoid specimens referable to Kroeyerina Wilson, 1932 (Kroyeriidae) and Brianella corniger Wilson, 1915 (Lernaeopodidae) were found on the spotback skate Atlantoraja castelnaui (Miranda Ribeiro, 1907), the smallnose fanskate Sympterygia bonapartii Müller & Henle, 1841, the bignose fanskate Sympterygia acuta Garman, 1877 and the zipper sand skate Psammobatis extenta (Garman, 1913) (Rajiformes: Arhynchobatidae). Additionally, specimens of B. corniger were found in the olfactory sacs of the Rio skate Rioraja agassizii (Müller & Henle, 1841) and attached to the pectoral fins of the Magellan skate Bathyraja magellanica (Philippi, 1902) and the smallthorn sand skate Psammobatis rudis Günther, 1870. A new species, Kroeyerina sudamericana sp. nov., is described and illustrated. The new species most closely resembles Kroeyerina nasuta Wilson, 1932, but can be distinguished from it by the different armature of the antennule, a proportionally shorter genital complex and the chela of the antenna which, when closed, leaves a gap between the corpus and claw, the latter having no spines. The new species represents the first record of Kroeyerina in South American marine waters. The present study also extends the distribution range of B. corniger, previously known only from the Pacific, to include Atlantic waters, and records seven new host species, all of which are members of the Arhynchobatidae.